2022
DOI: 10.1242/jeb.243674
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoid wasp venom manipulates host innate behavior via subtype-specific dopamine receptor activation

Abstract: The subjugation strategy employed by the jewel wasp is unique in that it manipulates the behavior of its host, the American cockroach, rather than inducing outright paralysis. Upon envenomation directly into the central complex (CX), a command center in the brain for motor behavior, the stung cockroach initially engages in intense grooming behavior, then falls into a lethargic sleep-like state referred to as hypokinesia. Behavioral changes evoked by the sting are due at least in part to the presence of the neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In addition to GABA, wasp venom contains dopamine ( Banks and Adams, 2012 ; Moore et al, 2018 ; Weisel-Eichler et al, 1999 ), which is shown to induce intense and prolonged grooming behavior. A recent study shows that the D1-like dopamine receptor (dopR) is the venom target responsible for grooming evoked by the sting into the CX ( Nordio et al, 2022 ). Furthermore, studies from Drosophila demonstrated that dopR receptors are highly expressed in the fly CX ( Kong et al, 2010 ; Pitmon et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to GABA, wasp venom contains dopamine ( Banks and Adams, 2012 ; Moore et al, 2018 ; Weisel-Eichler et al, 1999 ), which is shown to induce intense and prolonged grooming behavior. A recent study shows that the D1-like dopamine receptor (dopR) is the venom target responsible for grooming evoked by the sting into the CX ( Nordio et al, 2022 ). Furthermore, studies from Drosophila demonstrated that dopR receptors are highly expressed in the fly CX ( Kong et al, 2010 ; Pitmon et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, pharmacological studies extend the functional roles of the CX beyond locomotion, implicating its involvement in almost all the behavioral changes induced after the wasp sting. For example, pharmacological block of dopR receptors in the CX prior to the wasp sting prevents sting-induced grooming behavior ( Nordio et al, 2022 ) without affecting spontaneous walking. Likewise, focal injection of opiate agonists mimics venom effects on spontaneous walking and the escape threshold, but does not affect grooming behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation